(untitled) (The International Journal for Scientific Research, 2025)
Better communication is a significant process and necessary for the whole human community and all its activities. A good communication process is significant in all medical fields, especially psychiatry, where it affects examination, treatment, and patient well-being. It is considered a vital part of medical practice. Through combining traditional and modern studies. Effective communication is considered a pillar of medical practice, especially important in psychiatry, whereas it directly affects mutual understanding, diagnosis, treatment, and patient welfare. This article critically examines the great and complex role of communication in psychiatric therapy, synthesizing classical and current modern research to establish its advantages, limitations, and expected and potential improvements. Through a critical synthesis of literature from 2000 to 2023, the paper illustrates that good communication enhances patient outcomes, decreases medical errors, and strengthens the therapeutic relationship. Key barriers—language, culture, and the impact of mental disorders on communication is discussed, including evidence-based solutions for training, patient-centered care, skill, and technology integration. The results highlight the necessity of emphasizing communication skills and integrating it into medical education to ensure high-quality mental health care.